European sophisticated materialism versus American moral innocence - Moghadam, Davood Mohammadi; Wan Yahya, Wan Roselezam; Jujar Singh, Hardev Kaur (Support Foundation, 2014)
Henry James, as a prominent American novelist, is famous for his international novels, in which he practiced his famous international theme, to show the conflicts between America and Europe. It includes the conflicts between their societies, cultures, ideals, conventions and characters. James is called by Howells as the master of portraying the American girls, because usually, James practiced his international theme through portraying the American girls in the European society. It was through the adventures of these American girls that the conflicts between America and Europe are flourished in his international novels. In The wings of the Dove, through the adventure of Milly Theale, who is an American girl, James had tried to show the conflicts between America and Europe. These conflicts are mostly between American morality and European high culture, which is out of morality. This paper is going to discuss that in The wings of the Dove, James is complaining the materialistic Europe. It aims at representing that how the sophisticated materialism in European society is in contrast with morality of American innocence. The American innocence and European materialism propel the story of a deceived American in Europe, so the heroine, Milly Theale, who is an innocent American, is deceived by materialistic Europeans.